Anomalous decrease in groundwater radon before 2016 Mw 6.4 Meinong earthquake and its application in Taiwan. (June 2018) - Kuo, T.; Chen, W.; Ho, C.
Abstract: Recurrent groundwater radon anomalies were observed at the Paihe spring (P1) in southwestern Taiwan prior to the M w 6.3 Jiasian and M w 6.4 Meinong earthquakes that occurred on March 4, 2010 and February 5, 2016, respectively. Specifically, the concentration of groundwater radon decreased from background levels of 144 ± 7 and 137 ± 8 pCi/L to minima of 104 ± 8 and 97 ± 9 pCi/L prior to the 2010 Jiasian and 2016 Meinong earthquakes, respectively. The Paihe spring (P1) is located 46 km and 45 km, respectively, from the epicenters of the 2010 M w 6.3 Jiasian and 2016 M w 6.4 Meinong earthquakes. The above radon anomalies observed at the Paihe limestone spring corroborated that a small fractured aquifer can be used as an effective natural strain meter by applying radon as a tracer for earthquake warning in southwestern Taiwan. There are scientific difficulties and uncertainties in earthquake prediction. Nonetheless, a long-term monitoring of precursory declines in groundwater radon can provide useful data for forecasting local disastrous earthquakes. Highlights: Anomalous declines in groundwater radon were recorded before 2016 M w 6.4 Meinong earthquakes. A limestone aquifer can be a strain meter for earthquake warning by applying radon as a tracer. In-situ volatilization offers an attractive mechanism for a premonitory decrease in groundwater radon. A long-term monitoring of groundwater radon provides useful data for earthquake warning.